Novel Method for the Stochastic Generation of Hazard-Consistent Artificial Accelerograms: A practical application - Yanni, Hera; Fragiadakis, Michalis; Mitseas, Ioannis P. (Technical Annals, 2024)
In contemporary engineering practice, the investigation of the dynamic response of structures through time-history analysis requires the use of suites of acceleration ground motions. The paper studies the response of structures subjected to a novel methodology for the generation of target spectrum compatible artificial accelerograms. Existing spectrum-based models are used for the ground motion generation, whereas hazard consistency is achieved by matching these records either to a design spectrum or to a ground motion model. The obtained suites are used for the non-linear response history analysis (NRHA) of a benchmark multi-degree-of-freedom structure. Two study examples are presented. In the first example the generated suite matches only a spectral mean and in the second example the suite matches both the target spectral mean and variability. The results indicate that using the generated ground motion suites for the target NRHAs produces results that are consistent with record selection algorithms, thus confirming the efficiency of the proposed methodology.